Does injection flow rate have an impact on arterial phase image degradation in liver MRI? A comparison of gadoxetic acid versus gadobutrol. Issue 11 (November 2017) - Cohen-Hallaleh, V.; Guo, L.; Hosseini-Nik, H.; Razaghi Kashani, N.; Menezes, R.; Jhaveri, K.
Abstract : Aim: To evaluate retrospectively the impact of injection flow rate on arterial phase image degradation in liver magnetic resonance imaging (MRI) with gadoxetic acid (Gd-EOB-DTPA) compared to gadobutrol. Materials and methods: Two hundred consecutive patients who had undergone liver MRI were enrolled in this Health Insurance Portability and Accountability Act (HIPAA)-compliant institutional review board (IRB)-approved study and were divided into three groups. Group 1 (50 patients) and 2 (50 patients) had undergone MRI performed with gadoxetic acid (fixed 10 ml) at flow rate of 1 and 2 ml/s, respectively. Group 3 (100 patients) had undergone MRI performed with gadobutrol (0.1 mmol/kg) at 1 ml/s. Precontrast and post-contrast (arterial, portal venous, and hepatic venous phases) image degradation was assessed by two blinded independent readers using a four-point rating scale. The numbers of patients with arterial phase image degradation were compared using the Fisher exact test among the three groups. Results: The incidence of arterial phase image degradation was 12% (6/50) in group 1 and 16% (8/50) in group 2 for both readers, 6% (6/100) for reader 1 and 5% (5/100) for reader 2 in group 3. Group 2 had a higher incidence of arterial phase image degradation when compared with group 3 for reader 2 ( p =0.032). Severe arterial phase image degradation, resulting in non-diagnostic image quality, occurred in 4% (2/50) of patients when performed with gadoxetic acid administration at 2 ml/s and 2% (1/50) at 1 ml/s. Conclusion: A slower injection flow rate has a trend to reduce the incidence and severity of arterial phase image degradation during liver MRI with gadoxetic acid when compared to gadobutrol. Highlights: The incidence of arterial phase image degradation was 16% when Gd-EOB-DTPA (fixed 10 ml) was injected at a flow rate of 2 ml/sec. Severe arterial phase image degradation, resulting in non-diagnostic image quality, occurred in 4% of patients when performed Gd-EOB-DTPA administration at 2 ml/sec. Slower injection flow rate, reduced from 2 ml/sec to 1 ml/sec, has a trend to reduce the incidence and severity of arterial phase image degradation.